Improvement of rheological traits of dough made from winter wheat varieties through breeding - A. A. Sukhorukov (Зерновое хозяйство России, 2018)
А.А. Sukhorukov, Candidate of Agricultural Sciences, chief research officer; E.N. Shabolkina, Candidate of Agricultural Sciences, leading research officer; L.V. Pronovich, research officer of the laboratory of techno-analytical service FSBSI ‘Samara RIA’ (446254, Samara region, v. of Bezenchuk, Karl Marks Str., 41; tel.: 8 (84676) 2-11-40; email: samniish@mail.ru) Improvement of rheological traits of dough made from winter wheat varieties through breeding The article presents the study results of rheological traits of dough made from winter wheat varieties, which have been developed by the N.M. Tulaykov RIA in Samara in 2006-2015. The crop was sown in fallow land. The soil was blackearth (chernozem), medium loamy, medium-thick. The experiment was conducted four times. The area of the plots was 25m2. The rheological traits of dough made from winter wheat varieties were estimated according to the an average sample of grain by GOST R 51404 - 99. The amount of precipitation in the first decade of July (waxy maturity of kernels) was on less (1.0-3.4 mm) than the standard amount in 2006, 2010, 2014. In 2009 it corresponded to the norm, but it exceeded the norm four-fivefold in 2007, 2008 (62.6-86.1 mm with the norm of 15 mm). There have been determined high phenotypic variability of such traits as ‘dilute of dough’ (СV=39-71.3%), ‘stability of dough’ (СV=56-83.7%) and average phenotypic variability of the trait ‘valorimetric assessment’ (СV=20.5-29.9%). The dough made from the strong and valuable wheat varieties ‘Bezenchukskaya 380’ and ‘Bezenchukskaya 616’ possesses the most stable rheological properties. Under conditions of excessive humidity during the first decade of July (waxy maturity) the trait ‘dilute of dough’ negatively correlates with the volume of bread (r= - 0.86; Р 0.05) and total assessment of bread (r= - 0.53; Р 0.05). The valorimetric assessment positively correlates with the resistance of dough (r=0.92; P 0.05) and content of protein in kernels (r=0.52; P 0.05). Under insufficient humidity in the period of grain ripening (the period ‘flowering-waxy maturity’) (as happened in June 2015) the trait ‘resistance of dough’ positively correlates with content of protein (r=0.59; P 0.01) and gluten (r=0.60; P 0.01) in kernels. The valorimetric assessment positively correlates with the content of protein (r=0.62; P 0.01), content of gluten (r=0.72; P 0.01) and the resistance of dough (r=0.94; P 0.01). The trait ‘dilute of dough’ negatively correlates with a falling number (r= - 0.44; P 0.05). There have been selected the lines of winter wheat with the highest indexes of rheological properties of dough, namely moisture absorbing ability of flour (63.5-65.5%), time of dough and its stability (20-28 min), dilute of dough (30-50 u.f.), valorimetric assessment (97-100 u.v.) and a total assessment of bread (4.8-5.0 points).